PEMBELAJARAN DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR SISWA PADA PELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 11 KAMPUNG JUA PADANG - Syelfia Dewimarni; Mishbah Ulhusna; Lili Rismaini (Bajang Institute, 2022)
The Realistic Mathematics Education (RME) approach is one of the alternative learning approaches, the approach is very interesting and easy to apply, especially in mathematics because this approach refers to students' experiences and real or concrete objects. The goal to be achieved in this community service is to find out whether the Realistic Mathematics Education (RME) approach can increase students' motivation and interest in learning mathematics. The material presented during the research is on the shape of the space. The sample in this study were fourth grade students at SDN 11 Kampung Jua Padang with a total of 28 students. The type of research is descriptive research. Researchers describe students' motivation and interest during learning using the RME approach. The results of this study are that the fourthgrade students of SD Negeri 11 Kampung Jua have very high motivation and interest in learning during learning using RME.